Child care involvement of two groups of urban, low-income fathers and their toddlers' nutritional status - Pangan, Maria Raquel L. (2003)
The child care involvement of fathers and the impact of their caregiving on the nutritional status of their toddlers was studied. A structured questionnaire-interview method was used to obtain data from 288 fathers of intact families with 1 to 2-year-old children drawn by stratified random sampling from socio-economic levels D and E of Barangay Damayang Lagi, Quezon City. Urban poor fathers were more involved in the seven Psychosocial Care (PC) activities which provide emotional support and promote father-child communication than in the 12 Health and Nutritional Care (HNC) activities which ensure their toddlers' health, nutrition, and sanitation. The majority of the fathers usually performed 4 to 6 PC activities but only 1 to 5 HNC activities. Similarly, there was a high level of involvement in PC activities and only a moderate to low level of involvement in the HNC activities. The fathers' nature of child care involvement was negatively and weakly correlated with their toddlers' nutritional status measured in terms of weight-for-age. However, the levels of father involvement in child care were not significantly correlated with nutritional status. These correlation results were explained by classifying fathers according to "high" (those doing six of the twelve HNC and five of the seven PC activities) and "low" scorers (those doing 1 to 5 HNC and 1 to 4 of the seven PC activities). "Low" scoring fathers were found to have toddlers with normal weights while "high" scoring fathers were found to have underweight toddlers. In the case of PC activities, fathers having underweight or normal weight toddlers did not differ significantly in the number of psychosocial care activities they did from "low" scoring and "high" scoring fathers. Feeding practices, management of illness at home (taking care of sick child; waking up at night to give child medicine or food), and utilization of health services (bringing sick child to doctor/health center/hospital) are proximate determinants of a young child's nutritional status. The performance of these caring activities either enable the toddler to gain weight or help him recover lost weight due to a recent illness. "High" scoring fathers did two caring activities which can have a positive effect on the toddlers' weight (feeds child and takes care of a sick child) while "low" scoring fathers engaged themselves in only one activity: feeding the child. The disaggregation of low-income fathers into Class D (moderately poor) and Class E (very poor) socioeconomic categories revealed that Class E fathers were performing significantly more HNC and PC activities than Class D fathers. Similarly, Class E fathers registered a greater degree of involvement in both HNC and PC activities than Class D fathers. The association between fathers' involvement in HNC and the nutritional status of their toddlers seems to be homogenous. This was not modified by father's age, monthly income, the proportion of monthly income allocated to family expenses, or family socioeconomic status.